Sistem Toko Online Berbasis PHP Menggunakan Framework Bootstrap: Desty’s Pastry - Saputra, Muhammad Farhan; Wijaya, Anggi Hadi; ., Ipriadi (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
“Desty’s Pastry” previously relied on WhatsApp-based ordering and manual record-keeping, resulting in frequent order errors, limited market reach, and the absence of modern payment and notification features. This study aims to address these challenges by developing a web-based online store to improve operational efficiency and enhance customer experience. The system was built using the Waterfall development model, with requirements collected through interviews and direct observations. PHP 8.2, Bootstrap 5.3.5, and MySQL were used as core technologies, supported by Data Flow Diagrams and Entity Relationship Diagrams for system design. The resulting system provides key features including product catalog management, user authentication, shopping cart functionality, order processing, and an administrative dashboard, along with digital payment integration through QRIS. Black-box testing using Equivalence Partitioning showed that core functionalities such as registration, product selection, cart management, and order processing performed correctly with accurate data handling. Overall, the system successfully resolves initial operational issues and offers a scalable solution for SMEs adopting digital sales platforms.